Shields in Lithuania in the Old and Middle Iron Age - Kiulkys, Daumantas (Archaeologia Lituana, 2010)
[full article in Lithuanian; abstract in English]Shield was the most important defense instrument during battle in the period of Old and Middle Iron Age in Lithuania. Unfortunately, shield is the most under-researched weapon in Lithuanian archaeology. This article will try to fill part of this gap. The goal of this paper is to summarize the shield findings from Old and Middle Iron Age in Lithuania.Till now only metal shield parts from 66 archaeological sites are known in Lithuania. The biggest part of these findings is iron shield bosses which were found in all 66 sites (Map no 1). Up today 129 shield bosses were found during archeological excavations in Lithuania (Table no 1). Based on data of 60 shield bosses new their typology was made:Type I – shield bosses with semi-spherical top (Fig. 5–7). At least 9 specimens are known. All of them were found in Western Lithuania (Map no 2:a). Most of them are dated to 3rd century but some of them might belong to the end of the 2nd century or to the period of the 4th–5th centuries. Type 1 corresponds to N. Zieling types M and R1, which are distributed all over Central Europe and Scandinavia (Map no 2:b–d). These types are dated to phases C1a–C3 (220–350 AD).Type II – shield bosses with wall and semi-spherical top. Currently 4 specimens are known of this form, which can be divided into 3 variations.Variation A – shield bosses with wall and low semi-spherical top. This variation is represented by only 1 finding from Šaukėnai, Tauragė distr., grave No. 40 (Map no 3:a). Precisely it’s dating is unknown, but it should belong to the period of 3rd – beginning of the 5th centuries. Type IIA corresponds to N. Zieling type N, which is mostly distributed in Central Europe (Map No. 3:b). Two chronological groups of this type can be distinguished: early group dated to the end of La Tene period and the late group dated to phases C1b–C3 (220-350 AD).Variation B – shield bosses with wall and high semi-spherical top. Two specimens of this variation are known (Fig. 8–9) which belong to the first part or middle of 5th century.Variation C – shield bosses with wall and semi-spherical top which ends with apex (Fig. 10). Only 1 specimen of this variation is known found at Žvirbliai cemetery in Vilnius city. Precise it’s date is unknown but it should belong to the period of end of 4th–7th centuries.Type III – shield bosses with conical top which ends with flat cap. 5 specimens belong to this type. They can be divided into 3 variations.Variation A – shield bosses with conical top and concaved sides which end with flat cap (Fig. 11). 3 specimens belong to this type. Most of them should belong to phase C1 (150–260 AD) but some of them might be of later date, maybe even from beginning of the 5th century.Variation B – shield bosses with wall and conical top with concaved sides which end with round apex. Only 1 find from Dauglaukis, Tauragė distr., grave no 19 has this form. It belongs to period of 180–220 AD. Type IIIB corresponds to N. Zieling type B1b. Single findings of this type were found in Germany, Poland and Sambian peninsula (Map no 4:b) and are dated to phases C1a–C1b (150–260 AD). However, some of these specimens might belong to phase C2 (250–300 AD).Variation C – shield bosses with wall and conical top, which ends with cilindrical cap. Only 1 specimen of this type is known from Šarkai, Tauragė distr. (Fig. 12). Precise date of this finding is unknown but it definitely belongs to the period of 3rd–6th centuries. Type IIIC corresponds to N. Zielings type D1. Finds of this type are most common to the territories of Poland and Sambian peninsula (Map no 5:b). Most of these findings are dated to phase C1a (150–220 AD), but some of them might belong to phase C1b (220–260 AD).Type IV – shield bosses with faceted conical top (Fig. 13). Single item of this form is known from grave no 2 (Fig. 13:7) in Krikštonys, Lazdijai distr. It belongs to period the beginning of the 5th–6th centuries. Type IV corresponds to N. Zieling type T which is distributed in Southern Poland, Southern part of Czech Republic and Northern Hungary (Map no 6). Most of these finds belong to the period of second half of 4th – beginning of 5th centuries but some of them might be earlier and belong to phase C3 (300–350 AD).Type V – shield bosses with wall and conical top. This type is most common in Lithuania. It can be divided in to 6 variations.Variation A – shield bosses with wall and conical top which ends with apex. Currently single finding is known from cemetery in Stragnai, Klaipėda distr. (Fig.14). This type corresponds with J. Ilkjær type 3a and is dated to the beginning of 2nd – middle of the 4th centuries. Finding from Stragnai is probably of the same date.Variation B – shield bosses with two-pieces wall and rounded conical top with convexed sides. To this type belongs single item from barrow no 3 (Fig. 15) in Masiejūnai, Kaišiadorys distr. It is dated to the 5th century. This type corresponds with N. Zieling type L and is dated to phase C3 (300–350 AD). In Europe shield bosses of this form are mostly distributed in Southwest Poland and Sambian peninsula (Map no 7).Variation C – shield bosses with wall and high rounded conical top. Two specimens of this form are known (Fig. 16, 17). They are dated to the 5th–6th centuries.Variation D – shield bosses with wall and conical top (Fig. 18–22). This is the most common type of the shield bosses founded in Lithuania. At least 26 specimens are currently known. Most of them were founded in eastern and south-eastern parts of Lithuania. They are dated from the middle of the 3rd century to the beginning of the 7th century. Some specimens might be from later period and belong to the middle or even to the end of the 7th century. VD type corresponds with N. Zieling type H1 which is distributed all over Central Europe and Scandinavia. All of these findings belong to the period of the 1st century BC – middle of the 4th century AD.Variation E – shield bosses with concaved wall and conical top (Fig. 24–28). Currently, at least 9 items of this form are known from East, Southeast, South and Central Lithuania. They are dated to the 5th–6th centuries.Variation F – specimens of this variation look like VE type shield bosses, only their measurements are bigger. Two items of this form are known in Lithuania (Fig. 29, 30) and one in West Belarus (Fig. 31). Exact dating of these findings is unknown, but their similarity to VE type suggests that they belong to period of the 5th–7th centuries.Therefore currently 14 forms of shield boss are known in Lithuania, which belong to the middle of the 2nd–7th centuries (Fig. 32).Second most common shield part finding is the fitting of the shield handle. Currently 18 specimens are known from 12 archaeological sites (Map. no 2:b, c). Handle fitting from Dauglaukis, Tauragė distr., grave no 12 (Fig. 33) is the earliest of all items found and is dated to phase B2/C1. This finding is the only handle fitting which has analogies in Central Europe and Scandinavia. It corresponds to N. Zieling type G1 which is dated to phases B1–B2 (10–150 AD) and J. Ilkjær group 1 which is dated to the 1st century. Other handle fittings are mostly of two forms: fittings with convexed central part and widened ends (Fig. 7) and fittings.
Keywords: none